Issues and challenges associated with assessment reform in Malaysia, with particular focus on mathematics assessment - Khalid, Madihah (Institut Terjemahan & Buku Malaysia Berhad, 2016)
This chapter enables readers to analyse the implications of assessment reform in mathematics education. The readers are able to identify the issues and challenges behind the implementation of the curriculum.